Digital Wakafraising: Strategi Dalam Mengoptimalkan Wakaf Uang Pada PT Edukasi Wakaf Indonesia - Agriana, Gita; Taufiqur Rahman (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2025)
Most nazhirs in Indonesia face problems related to the collection of cash waqf due to minimal literacy and education about cash waqf in society. Indonesia itself has enormous potential for cash waqf, but in realit, it has not been utilized optimally. With the development of waqf digitalization, it is hoped that it can increase the efficiency of cash waqf collection. This research aims to analyze the optimization of digital waqf collected in cash waqf. This research uses a qualitative approach with field studies, with primary data obtained from primary sources including stakeholders and experts in the field of waqf at PT Edukasi Wakaf Indonesia. Data analysis techniques use data reduction, data presentation, and conclusion drawing. The results show that digital marketing strategies through social media, educational programs, waqfraiser and nazhir training support the optimization of cash waqf in waqf institutions. The impact of easy access and transparency in fund management will increase public participation in implementing cash waqf in Indonesia.